Effect of low-and high-carbohydrate diets on swimming economy: A crossover study - Bestard, M. A.; Rothschild, J. A.; Crocker, G. H. (Journal of the International Society of Sports Nutrition, 2020)
Background: Swimming economy refers to the rate of energy expenditure relative to swimming speed of movement, is inversely related to the energetic cost of swimming, and is as a key factor influencing endurance swimming performance. The objective of this study was to determine if high-carbohydrate, low-fat (HCLF) and low-carbohydrate, high-fat (LCHF) diets affect energetic cost of submaximal swimming.